Pengaruh Kapasitas Penampungan Air terhadap Hasil Pengomposan Sampah Pasar Organik - Destiasari, Ajeng; Sumiyati, Sri; Istirokhatun, Titik (Politeknik Negeri Lampung., 2023)
The increasing volume of market waste that continues to occur makes people think negatively of waste, but on the other hand waste can provide positive things by composting. The purpose of this research is to analyze the content of Water Holding Capacity (WHC) in organic compost made from market waste. The composting process uses the Open Windrow method with aerobic Composting Bag container media. Composting was carried out for fifteen days with variations in the addition of bioactivators to accelerate the maturation of different composts are 50 ml, 75 ml, 100 ml, 125 ml, and 150 ml with one control compost. The bioactivator used is a type of local microorganism (MOL) made from market waste. Based on the results of this study, compost with a variation of 150 ml bioactivator addition produced an optimal WHC content of 75%, the best water content of 49.24%, C/N 15.57%, temperature 32.29°C, and pH 7.